EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2016)
Teacher education today requires greater strategic planning and collaboration, both within teacher education and in partnerships with teachers and schools. Such endeavours require new competencies – both for the preservice teachers and teacher educators. Researchers have commented that there is a gap between what beginning teachers require in their practice and what teacher education prepares them. With the advent of technology, digital competence appears to be an area that also need more focus and interpretation. This issue of the Journal of Research, Policy & Practice of Teachers & Teacher Education looks at all these issues and discusses examples of some of the important steps we need to take through research-based knowledge within teacher education.